(untitled) (Movimenta (ISSN 1984-4298), 2023)
The assessment of cardiorespiratory functional capacity can contribute to the prognosis of cardiovascular, chronic respiratory and musculoskeletal system diseases, considering loss of functional capacity and the presence of comorbidities. This evaluation can be done through maximal tests such as the cardiopulmonary exercise test, exercise test and submaximal tests such as the 6-minute walk test (6MWT) and the 6-minute step test (6MST). There are few studies that compare both tests and can validate the replacement of the 6MWT by the 6MST, since the 6MWT is a test that requires a large space to be performed, unlike the 6MST, which only needs a 20 cm high step. The objective of the present study was to verify the correlation between the 6MST and the 6MWT in the evaluation of the functional capacity of the elderly. Cross-sectional descriptive study with voluntary non-probabilistic sampling, consisting of 28 elderly people who are part of the Cardiovascular Physiotherapy in Primary Care study. The sample was submitted to the 6MWT and 6MST, and the beginning and end parameters were collected to be compared. The submaximal exercise capacity was evaluated by the distance covered in the walking test and by the number of ascents and descents of the step, and equations were performed to obtain the VO2max of both tests. The sample had a mean age of 69.86 ± 7.34 years (75% female). There was a positive and moderate correlation between the estimated values for VO2max in the walk and step test (p = 0.01 and r = 0.57) and between the distance covered in the walk test and the number of ascents and descents in the step test (p = 0.02 and r = 0.43). The six-minute step test can be an alternative to assess the functional capacity of the elderly.